INTERPERSONAL COMMUNICATION AND DIGITAL TECHNOLOGY IN THE ACADEMIC PRACTICES OF ISLAMIC HIGHER EDUCATION STUDENTS - Ria Hayatunnur Taqwa; Raziki Waldan; Pilga Ayong Sari (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
This study examines the role of interpersonal communication and digital competence in the completion of final projects among students at IAIN Pontianak. The background of this study lies in the increasing challenges in completing final projects due to limited effective communication with academic advisors and insufficient digital skills. The research employs a qualitative approach with a case study method. Data were collected through semi-structured interviews, participatory observations, and documentation involving 15 students and 5 academic advisors. The findings reveal that intensive interpersonal communication and adequate digital competence support the timely completion of final projects. However, some students face technological limitations and communication barriers that hinder progress. The contribution of this study lies in proposing an integrated framework of interpersonal communication and digital competence as a holistic approach in academic supervision, while also highlighting the psychosocial dimension of student mental well-being. The conclusion emphasizes the importance of developing technology-based academic supervision policies and providing psychological support in Islamic higher education to enhance the quality of final project completion.